Characterization of Ionic and Lipid Gradients within Corpus Callosum White Matter after Diffuse Traumatic Brain Injury in the Rat - Hartnell, David; Gillespie-Jones, K.; Ciornei, C.; Hollings, Ashley; Thomas, Alexander; Harrild, Elizabeth; Reinhardt, J.; Paterson, D.J.; Alwis, D.; Rajan, R.; Hackett, Mark (AMER CHEMICAL SOC, 2020)
There is increased recognition of the effects of diffuse traumatic brain injury (dTBI), which can initiate yet unknown biochemical cascades, resulting in delayed secondary brain degeneration and long-term neurological sequela. There is limited availability of therapies that minimize the effect of secondary brain damage on the quality of life of people who have suffered TBI, many of which were otherwise healthy adults. Understanding the cascade of biochemical events initiated in specific brain regions in the acute phase of dTBI and how this spreads into adjacent brain structures may provide the necessary insight into drive development of improved therapies. In this study, we have used direct biochemical imaging techniques (Fourier transform infrared spectroscopic imaging) and elemental mapping (X-ray fluorescence microscopy) to characterize biochemical and elemental alterations that occur in corpus callosum white matter in the acute phase of dTBI. The results provide direct visualization of differential biochemical and ionic changes that occur in the highly vulnerable medial corpus callosum white matter relative to the less vulnerable lateral regions of the corpus callosum. Specifically, the results suggest that altered ionic gradients manifest within mechanically damaged medial corpus callosum, potentially spreading to and inducing lipid alterations to white matter structures in lateral brain regions.